Unequal crime decline: theorizing race, urban inequality, and criminal violence - Parker, Karen Faye (New York Univ. Press, 2008)
Introduction -- The difference race and gender makes : a detailed look at violent crime and the crime drop -- Structural perspectives on crime and their critics -- Racial stratification and the local urban economy -- Race, urban inequality, and the changing nature of violence : an illustration of theoretical integration 98 -- Conclusion